Development of a sixth-order active elliptic bandpass filter for cellular base station receiver and transmitter applications - Atsuwe B Aondofa; Atser R Akpenongun (Physics Access, 2025)
This paper presents the design and simulation of a sixth-order active elliptic bandpass filter intended for cellular base station receiver and transmitter applications. The filter is designed to operate at a centre frequency of 2.65 GHz with a bandwidth of 100 MHz, employing a combination of elliptic filter synthesis and active filter design techniques. Simulation results yield a centre frequency of 2.653 GHz, a bandwidth of 100 MHz, and a passband gain of −35.124 dB. Additional performance metrics include a passband ripple of 0.5 dB, stopband attenuation of 60.145 dB, group delay of 2 ns, noise figure of 2.5 dB, insertion loss of 0.016 dB, return loss of 2.558 dB, and power consumption of 50 mW. The results confirm that the filter meets the required design specifications and is suitable for high-frequency, low-power applications in modern cellular infrastructure